Pengetahuan, Sikap dan Kepatuhan Protokol Kesehatan Pasca Vaksinasi Covid-19 - Jessica Naomi Sahmauli; Acim Heri Iswanto; Laily Hanifah; Yuri Nurdiantami (FORIKES, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Currently, there are several mutations in virus variants that change the nature of the virus to make it easier to spread, thus affecting vaccine performance. After people receive the COVID-19 vaccine, what is feared is that people feel they are already immune, so they relax health protocols, even though the COVID-19 variant can reduce the effectiveness of the vaccine. The purpose of this study was to determine the relationship between knowledge and attitudes and adherence to health protocols after the COVID-19 vaccination in Lebak Bulus, South Jakarta in 2021. The type of research used was a quantitative cross-sectional approach, with a sample size of 125 people. Data was collected by filling out questionnaires, then analyzed descriptively and a correlation analysis was performed using the Chi-square test. The results showed that the value of p = 0.000 for the knowledge factor and p = 0.002) for the attitude factor. It was concluded that knowledge and attitudes were related to adherence to implementing health protocols. The people of RW 08 Lebak Bulus are advised to maintain compliance with health protocols and RW/RT administrators are advised to remind the public to continue to comply with health protocols.Keywords: COVID-19; compliance with health protocols; knowledge; attitude ABSTRAK Coronavirus Disease 2019 (COVID-19) adalah penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Saat ini terdapat beberapa mutasi varian virus yang mengubah sifat virus menjadi lebih mudah menyebar hingga memengaruhi kinerja vaksin. Setelah masyarakat menerima vaksin COVID-19 yang dikhawatirkan adalah masyarakat merasa sudah kebal sehingga melonggarkan protokol kesehatan, padahal varian COVID-19 dapat menurunkan tingkat efektivitas vaksin. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan dan sikap dengan kepatuhan protokol kesehatan pasca vaksinasi COVID-19 di Lebak Bulus Jakarta Selatan tahun 2021. Jenis penelitian yang digunakan adalah kuantitatif dengan pendekatan cross-sectional, dengan ukuran sampel 125 orang. Data dikumpukan melalui pengisian kuesioner, lalu dianalisis secara deskriptif dan dilakukan analisis korelasi menggunakan uji Chi-square. Hasil penelitian menunjukkan nilai p = 0,000 untuk faktor pengetahuan dan p = 0,002) untuk faktor sikap. Disimpulkan bahwa pengetahuan dan sikap berhubungan dengan kepatuhan melaksanakan protokol kesehatan. Bagi masyarakat RW 08 Lebak Bulus disarankan untuk mempertahankan kepatuhan melaksanakan protokol kesehatan dan kepada pengurus RW/RT disarankan untuk mengingatkan masyarakat agar tetap mematuhi protokol kesehatan.Kata kunci: COVID-19; kepatuhan protokol kesehatan; pengetahuan; sikap